Dilemma in metastatic colorectal cancer: VEGF versus EGRF targeting. (August 2013) - Rolfo, Christian; Russo, Antonio; Santini, Daniele; Bronte, Giuseppe; Peeters, Marc
Abstract : The modern approach for metastatic colorectal cancer (mCRC) patients is based on the identification of oncogenic pathways, which could be targeted by specific molecules. Vascular endothelial growth factor (VEGF)- and epithelial growth factor receptor (EGFR)-related pathways represent the most important biological mechanisms for cancer development and progression. However, the most significant results by VEGF and EGFR targeting could be achieved through the combination of these drugs with standard chemotherapeutic regimens. These strategies aim to improve the resectability of liver and lung metastases. For those patients who cannot be eligible for metastases resection, a 'continuum of care' has been proposed as the best option. This strategy includes the sequential delivery of various regimens with different targeted drugs. For this reason the choice of the pathway to target, that is, VEGF or EGFR, is not a real dilemma since both these molecules would be targeted during the mCRC natural history. To date, a selection by KRAS mutational status is mandatory to identify those patients with higher probability of benefit from anti-EGFR monoclonal antibodies. In this case VEGF targeting is the only way to choose. New molecules are under evaluation to widen these treatment options.